2019
DOI: 10.1101/707596
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Germ Granules Coordinate RNA-based Epigenetic Inheritance Pathways

Abstract: Germ granules are biomolecular condensates that promote germ cell totipotency in most, if not all, animals. In C. elegans, MEG-3 and MEG-4 are two intrinsically disordered proteins that are redundantly required for the phase separations that drive germ granule assembly in germline blastomeres. Here, we show that animals lacking MEG-3/4 exhibit defects in dsRNA-mediated gene silencing (RNAi) that are due, at least in part, to defects in systemic RNAi. Interestingly, these RNAi defects are transgenerationally di… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 59 publications
6
37
0
Order By: Relevance
“…It is also possible that the role of Z granules in germline RNAi is indirect, as previous studies have shown that disrupting germ granules can indirectly affect RNAi responsiveness in C. elegans (Dodson & Kennedy, 2019; Ouyang et al , 2019; Lev et al , 2019). For instance, the intrinsically disordered proteins MEG‐3 and MEG‐4 (MEG‐3/4) promote P granule assembly and are, like ZSP‐1, required for germline RNAi (Dodson & Kennedy, 2019; Ouyang et al , 2019). The germline RNAi defect associated with meg‐3/4 is indirect in that RNAi defects are due to HRDE‐1‐dependent aberrant silencing of rde‐11 / sid‐1 and not because P granule formation is itself necessary for germline RNAi (Dodson & Kennedy, 2019; Ouyang et al , 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also possible that the role of Z granules in germline RNAi is indirect, as previous studies have shown that disrupting germ granules can indirectly affect RNAi responsiveness in C. elegans (Dodson & Kennedy, 2019; Ouyang et al , 2019; Lev et al , 2019). For instance, the intrinsically disordered proteins MEG‐3 and MEG‐4 (MEG‐3/4) promote P granule assembly and are, like ZSP‐1, required for germline RNAi (Dodson & Kennedy, 2019; Ouyang et al , 2019). The germline RNAi defect associated with meg‐3/4 is indirect in that RNAi defects are due to HRDE‐1‐dependent aberrant silencing of rde‐11 / sid‐1 and not because P granule formation is itself necessary for germline RNAi (Dodson & Kennedy, 2019; Ouyang et al , 2019).…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, and because P granules localize directly adjacent to nuclear pores, it has been suggested that P granules are major sites of small RNA-directed mRNA surveillance in C. elegans germ cells (Wang & Reinke, 2008;Batista et al, 2008;Claycomb et al, 2009;Gu et al, 2009;Beshore et al, 2011). Consistent with this idea, mutations that disrupt P granule formation cause misexpression of somatic and sperm mRNAs within oogenic germlines and cause small regulatory RNA-based gene regulation to become disorganized and defective (Spike et al, 2008;Campbell & Updike, 2015;Spracklin et al, 2017;Knutson et al, 2017;Dodson & Kennedy, 2019;Ouyang et al, 2019). Other compartments of the perinuclear nuage are also thought to function in distinct, yet related aspects of small RNA-based gene regulation.…”
Section: Introductionmentioning
confidence: 97%
“…However, it is only recently that a role for the P granule in ensuring appropriate small RNA-mediated silencing has been shown. Using mutant animals that lack P granules in the C. elegans primordial germ cells, these studies elegantly show that P granules are required for transgenerational inheritance of RNAi 44 , 50 , 51 . The direct interaction between PRG-1 and DEPS-1 provides an example for how small RNAs and P granules can be biochemically coupled.…”
Section: Discussionmentioning
confidence: 99%
“…6c). deps-1 also affects wago targets 44 (300 out of 425 wago targets show > twofold reduction in 22Gs level in deps-1 mutant; Hypergeometric Test: p < 10 −139 ; Fig. 4d and Supplementary Fig.…”
Section: Deps-1 Binds To Prg-1 Via Its Piwi Binding Site (Pbs)mentioning
confidence: 99%
“…Recent studies in C. elegans have shown that piRNA/ PRG1-dependent mRNA accumulation in germ granules prevent their silencing, strengthening the function of piRNAs in germ granules for mRNA storage and surveillance. 56,57 In Drosophila, Aub mediates the link between piRNAs and mRNA regulation in germ granules since Aub localization to germ granules depends on its loading with piRNAs 12 and Aub/piRNAs play a general role in the localization and stabilization of germ cell mRNAs in germ granules. 13,19 How do germ granules accommodate translational control has remained more elusive.…”
Section: Discussionmentioning
confidence: 99%